2016
DOI: 10.3847/0004-637x/825/2/125
|View full text |Cite
|
Sign up to set email alerts
|

RAPID CIRCUMSTELLAR DISK EVOLUTION AND AN ACCELERATING STAR FORMATION RATE IN THE INFRARED DARK CLOUD M17 SWex

Abstract: We present a catalog of 840 X-ray sources and first results from a 100 ks Chandra X-ray Observatory imaging study of the filamentary infrared (IR) dark cloud G014.225-00.506, which forms the central regions of a larger cloud complex known as the M17 southwest extension (M17 SWex). In addition to the rich population of protostars and young stellar objects with dusty circumstellar disks revealed by archival data from the Spitzer Space Telescope, we discover a population of X-ray-emitting, intermediate-mass pre-m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(79 citation statements)
references
References 103 publications
4
75
0
Order By: Relevance
“…In general, deeply embedded YSOs (red stars as stage 0/I sources; Povich et al 2016) are found to be associated with hubs and filaments while evolved YSOs (blue stars as stage II/III and blue crosses as X-ray sources; Povich et al 2016) appear more distributed in the regions. Dense cores identified in the continuum studies (brown open circles; Ohashi et al 2016) are preferentially located in hubs, and just a few in filaments.…”
Section: Observationsmentioning
confidence: 98%
“…In general, deeply embedded YSOs (red stars as stage 0/I sources; Povich et al 2016) are found to be associated with hubs and filaments while evolved YSOs (blue stars as stage II/III and blue crosses as X-ray sources; Povich et al 2016) appear more distributed in the regions. Dense cores identified in the continuum studies (brown open circles; Ohashi et al 2016) are preferentially located in hubs, and just a few in filaments.…”
Section: Observationsmentioning
confidence: 98%
“…The HII region (M17-HII region) surrounding the cluster has opened a large gap at its edge which lets stellar radiation and winds escape exciting a diffuse X-Ray emitting region observed with the Chandra Observatory (Townsley et al 2003). In addition to the relatively mature HII region around the cluster, other notable star-forming regions have been discovered in the vicinity of M17 such as the immediate environment of M17 (Ando et al 2002), or the M17 Infrared Dark Cloud (M17-IRDC, also known as M7-SWex) that contains the IRDC G14.225-0.506 (Povich & Whitney 2010;Povich et al 2016;Ohashi et al 2016). M17 forms a larger molecular cloud complex together with M16 cloud as suggested by Nguyen-Luong et al (2016).…”
Section: Overview Of the M17 Regionmentioning
confidence: 99%
“…Interestingly, a second compression at the interface of the M17-HII region when the OB star clusters compress the edge of the cloud also occured which can be seen in CO (J = 3 − 2) (Rainey et al 1987) and also in high density tracer such as HCN (J = 4 − 3) (White et al 1982). From the Spitzer observations, Povich & Whitney (2010) and Povich et al (2016) discovered that the mass function of young stellar objects (YSOs) around the M17-HII region seems consistent with the Salpeter IMF, whereas that in the M17-IRDC is significantly steeper than the Salpeter IMF. In other words, the high-mass stellar population in M17-IRDC is deficient.…”
Section: Overview Of the M17 Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…formation rate ≥ 0.004 M ⊙ yr −1 (see Povich et al 2016, and references therein). Chibueze et al (2016) identified hundreds of H 2 O maser sources in the M17 region spanning a local standard of rest velocity (v LSR ) range of 14.0-22.0 km s −1 .…”
Section: Selected Regionsmentioning
confidence: 99%